Maternal Stress Experience in the Neonatal Intensive Care Unit after Preterm Delivery - Pavlyshyn, Нalyna; Sarapuk, Iryna; Saturska, Uliana (American Journal of Perinatology, 2022)
Objective Preterm delivery with the admission of a child in the neonatal intensive care unit (NICU) is extremely challenging for parents. Being separated from the baby and seeing her infant feeling pain and being sick together with the complexity of the NICU environment, the mother experiences great anxiety, fear, and stress. The purpose of the study was to assess NICU-related stress and to identify maternal and infant factors associated with increased stress in mothers of preterm infants.Study Design The maternal stress level was assessed in 122 mothers of preterm infants using the Parental Stressor Scale: NICU (PSS: NICU) in which items were distributed in three subscales as follows: Sights and Sounds of NICU—subscale 1 (S1), Infant Appearance and Behavior—S2, and Parental Role Alteration—S3.Results Maternal total PSS: NICU score was 3.46 ± 0.71. Parenteral Role Alteration was the most stressful (4.20 ± 0.79) followed by Infant Appearance and Behavior (3.51 ± 0.91) and Sights and Sounds subscale (2.28 ± 0.95); p(S1–S2) < 0.001, p(S1–S3) < 0.001, and p(S2–S3) < 0.001. Total PSS: NICU and Infant Appearance and Behavior scores correlated positively with maternal age (r = 0.189; p = 0.040 and r = 0.204; p = 0.027, respectively) and duration of NICU treatment (r = 0.188; p = 0.044 and r = 0.190; p = 0.042). More visits in NICU by a mother were associated with a lower PSS: NICU score (p = 0.049) and neonatal seizures and invasive ventilation in infants were associated with higher stress scores (p = 0.007 and p = 0.042).Conclusion Mothers of preterm infants admitted in the NICU experience significant stress which is correlated with maternal age and NICU treatment duration and is associated with frequency of NICU visits, presence of neonatal seizures, and need for ventilator support. Parental role alteration is the greatest stressor followed by Infant Appearance and Behavior and NICU-surrounding stressor factors which show the need for interventions and counseling focused on mothers' role, their involvement in infant's care, and thus, family-centered care implementation.Key Points
Keywords: maternal stress; parental stressor scale: neonatal intensive care unit questionnaire; parental role alteration; preterm infants